The role of retroviral cyclin in the development of walleye dermal sarcoma - Birkenheuer, Claire, author; Rovnak, Joel, advisor; Quackenbush, Sandra L., advisor; Nyborg, Jennifer, committee member; VandeWoude, Susan, committee member; Wilusz, Jeff, committee member (Colorado State University. Libraries, 2015)
The retroviral cyclin (RV-cyclin) is an accessory protein encoded by walleye dermal sarcoma virus (WDSV). This virus causes the formation of walleye dermal sarcoma, and requires the tumor tissue to replicate. RV-cyclin is one of only two proteins expressed by the virus during tumor development before production of the WDSV virion, and the mechanism by which RV-cyclin causes tumor formation was explored and is presented here. RV-cyclin interacts with TAF9 and CDK8, which are cellular proteins that regulate RNA Pol II transcription. RV-cyclin's influence on transcription was explored by analyzing transcript levels of CCND1, CDKN2D, FOS, EGR1, and JUN. All of these genes are important oncogenes in human cancers, and were hypothesized to contribute to development of walleye dermal sarcoma (WDS). Quantitative reverse transcription PCR analysis of these genes in HeLa and HCT116 cell lines expressing wt or mutant RV-cyclin, or over-expressing cyclin C was carried out. These analyses showed that wt RV-cyclin enhances expression of all genes tested and that the interactions with TAF9 and with CDK8 contribute to this enhancement. Western blot analysis of phosphorylated Elk1 and SRF, two transcription factors that initiate RNA Pol II transcription, revealed that RV-cyclin's mechanism of gene activation is downstream of transcription factor phosphorylation. Messenger RNA (mRNA) decay assays demonstrated that RV-cyclin does not alter the rate of mRNA decay, framing RV-cyclin's mechanism of activation to the level of RNA Pol II transcription. Nuclear run-on and chromatin immunoprecipitation analysis of EGR1 with an RNA Pol II antibody support a role for RV-cyclin in transcription elongation and re-initiation. ChIP analysis of the mutant RV-cyclin cells and cells over-expressing cyclin C demonstrated that RV-cyclin requires both a functional CDK8 and TAF9 interaction for efficient activation and extension of the EGR1 serum response. CDK8 ChIPs demonstrated that the RV-cyclin enhances CDK8 occupancy at the EGR1 gene locus, and HA-ChIPs show that CDK8 and RV-cyclin occupancy correlate with each other on the locus. At this point, it was hypothesized that RV-cyclin functions to enhance CDK8 kinase activity in addition to bringing more CDK8 to select oncogenic loci in vivo. For this reason kinase assays using recombinant, baculovirus-produced CDK8/RV-cyclin or CDK8/cyclin C constructs were attempted. CDK8 bound to RV-cyclin was able to autophosphorylate to similar levels as CDK8 bound to cyclin C. Other CDK8 substrates remain to be tested. RV-cyclin's function in transcription requires activation of the MAPK pathway, suggesting RV-cyclin needs an outside signal like serum stimulation for efficient WDS formation. This signal likely comes from the presence of the Orf b protein, the other WDSV accessory protein expressed during tumor development. The protein Orf b causes phosphorylation and activation of the p90RSK complex. This event likely causes aberrant phosphorylation of SRF and Elk-1 giving RV-cyclin the activated transcription factors required for its function on specific proto-oncogenes. Taken together, the Orf b protein and RV-cyclin illustrate a previously un-described, trans-acting mechanism of retroviral-induced oncogenesis.
Keywords: retroviral cyclin; CDK8; walleye dermal sarcoma virus